Gas exchange variables as promising criteria for screening freezing‐tolerant faba bean (Vicia faba L.) landraces at early growth stages. Issue 1 (22nd January 2021) - Nabati, Jafar; Hasanfard, Alireza; Nezami, Ahmad; Ahmadi‐Lahijani, Mohammad Javad; Boroumand Rezazadeh, Elaheh
Abstract: Photosynthesis is one of the parameters first affected by freezing stress. So studying the efficiency of photosynthetic parameters could be an effective strategy in screening freezing‐tolerant genotypes. An experiment was conducted to assess freezing temperature effects (0°C, −4°C, −8°C, −12°C, −16°C, −20°C, and −24°C) on two faba bean landraces (Borujerd and Neyshabur). Leaf chlorophyll and carotenoid content were decreased as the temperature declined below 0°C. Net photosynthetic and transpiration rate declined earlier in Neyshabur, whereas a relatively constant trend was observed in Borujerd at temperatures between 0°C and −12°C. A 43% greater N p was recorded in Borujerd than Neyshabur at −12°C. N p recovered by 30% and 36% in Borujerd and Neyshabur, respectively, on Day 14 compared with the second day of the recovery period. Except for C i, which showed a relatively constant trend, the other parameters showed a decreasing trend till 7 days after freezing stress (DAF). WUEi increased more significantly in Neyshabur than in Borujerd after the seventh day of the recovery period. With a subtle evaluation of the landraces' freezing tolerance, both landraces LT50su and RDMT50 remained up to −10°C and −12.5°C, respectively, indicating faba bean plants (the landraces here) can tolerate freezing stress up to −10°C (by enduring minor damages). The positive relationship between the survival percentage and N p indicated that N p could be a reliable criterion to screen freezing‐tolerant faba beans at early growth stages.